Trypanoxyuris atelis and T. atelophora (Nematoda: Oxyuridae) in wild spider monkeys (Ateles geoffroyi) in tropical rain forest in Mexico: Morphological and molecular evidence. Issue 5 (October 2015) - Solórzano-García, Brenda; Nadler, Steven A.; Pérez Ponce de León, Gerardo
Abstract Two species of pinworms, Trypanoxyuris atelis and Trypanoxyuris atelophora were collected from the black-handed spider monkey (Ateles geoffroyi) in several localities across southeastern Mexico, representing the first record for both species in Mexican primates. Identification of pinworm species was based on morphological and molecular data. These pinworms are distinguished from other congeners, and from each other, by the buccal structure, the lateral alae, and the morphology of the oesophagus. Phylogenetic analyses based on sequences of the mitochondrial cytochrome c oxidase subunit 1 gene placed T. atelis as the sister species of Trypanoxyuris minutus, a parasite of the howler monkey Alouatta palliata, and T. atelophora as the sister species of T. microon, a parasite of the night monkey, Aotus azarae. These relationships were supported with high posterior probability values by Bayesian inference. Comparisons of additional pinworm taxa from Neotropical primates are needed to assess oxyurid diversity, and to better understand the evolutionary relationships among these nematodes and their primate hosts.